Atherosclerosis and inflammation – the path from pathogenesis to treatment: review of the current state of the issue (part 2) - A. A. Avagimyan; L. V. Kaktursky; O. I. Urazova; A. I. Trofimenko; L. M. Sukiasyan; E. A. Kogan; T. A. Demura; N. V. Pogosova (Бюллетень сибирской медицины, 2025)
Numerous studies addressing the fundamental aspects of atherosclerosis emphasize the importance of systematically organizing the accumulated data. The second part of this lecture provides an analysis of the critical mechanisms involved in the development of atherosclerosis. This analysis includes a discussion on the roles of inflammasomes, hemodynamic disorders within the vascular wall, vasa vasorum pathology, endothelial cell dysfunction, matrix metalloproteinases, and the Notch and Wnt signaling pathways in the process of atherogenesis. Additionally, it explores the specific characteristics of the pathogenesis of vascular calcification associated with atherosclerosis. A dedicated section thoroughly reviews contemporary pharmacotherapeutic strategies for managing atherogenic dyslipidemia. A comprehensive analysis of current concepts regarding the pathogenesis of atherosclerosis, along with promising approaches to drug therapy, will facilitate the identification of future research directions within the field of lipidology. This endeavor has the potential to elevate preventive cardiology to a new standard.